PENGARUH PEPSEPSI RISIKO PADA PERILAKU PHYSICAL DISTANCING MASYARAKAT DI MASA PANDEMI - Karsiyati, Karsiyati; H, Widyaning (Psikologi UHAMKA, 2021)
In various studies, the perception of risk was referred as a predictor of a person's healthy behavior. In other words, risk perception affected behavior related to protective health behavior, including physical distancing to reduce transmission of Covid-19. Uniquely, it is seen that the public are neglecting the physical distancing policy, eventhough they are actually worrying about the virus transmission. This fact makes the researcher wants to know the actual effect of risk perception on physical distancing in Indonesian society. Especially considering the communication style between the media and the government when Covid-19 began to spread in many regions, emphasizing the risk of transmission and the impact. Data collection was carried out using a risk perception scale and physical distancing behavior through online for 624 respondents. Regression analysis was used to answer research questions. From the results of the study, it was found that there was an influence of risk perception on people's physical distancing behavior in the Covid-19 pandemic era, even though the effect was relatively small.